(untitled) - Moore, Richard H. (London, 1990)
Introduces some pattern of rural development of Japanese agriculture
Keywords: Rural development,Agriculture and state,Nông nghiệp và quốc gia,Phát triển nông thôn; Japan,Japan,Nhật Bản,Nhật Bản